GSK-3β and memory formation - Takashima, Akihiko (Frontiers in Molecular Neuroscience, 2012)
In Alzheimer’s disease (AD), tau hyperphosphorylation and neurofibrillary tangle (NFT) formation are strongly associated with dementia. Memory impairment is a characteristic, early symptom of AD. Glycogen synthase kinase 3 β (GSK-3β), which is activated in response to amyloid β (Aβ) formation, and the normal process of aging, hyperphosphorylates tau present in the NFTs. Furthermore, activation of GSK-3β inhibits synaptic long-term potentiation (LTP) through tau. It is therefore likely, that activation of GSK-3β is responsible for the memory problems seen in both advanced age, and AD. Indeed, inhibition of GSK-3 by lithium halts the progression of symptoms in patients with mild cognitive impairment (MCI). However, long-term treatment of lithium increases the risk of dementia in old age, in bipolar patients. To understand the role of GSK-3β in brain function, we analyzed memory formation in GSK-3β heterozygote, knockout mice. Results indicate that these mice show impaired memory reconsolidation. It would seem that activation of GSK-3β is required for memory maintenance, with a higher requirement as animals age, and the volume of memory increases. This in turn causes exaggerated activation of GSK-3β, leading to memory problems, and the formation of NFTs.